Economic Analysis of International Law Contributions to the XIIIth Travemünde Symposium on the Economic Analysis of Law (March 29-31, 2012) - Eger, Thomas; Voigt, Stefan; Oeter, Stefan (Mohr Siebeck, 2014)
The topics covered in this volume range from classics of the on-going discussion on the economic analysis of international law - such as the issue of legitimacy of customary international law - to more recent topics such as internet privacy, private military contractors, the fight against piracy, the International Criminal Court and the highly topical issue of land grabbing.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Law / International; Law; Electronic books